Educação inclusiva na educação infantil - Carneiro, Relma Urel Carbone [UNESP] (My University, 2012)
This paper aims to trigger a reflection on inclusive education in early childhood education, considering education as an inclusive educational model endorsed by public policies, but still far from school reality. The reflection aims to think about necessary changes since early childhood education,because this is the first stage of basic education and it is a critical period in development and learning process of children with disabilities. The construction of the inclusive school since early childhood education involves thinking about its space, time, professional, educational resources etc..,turning to the possible access, retention and development to students with disabilities, students that, because of their particular characteristics, have a special educational necessity. The text discusses, among other things, the necessity to rethink pedagogical practice as a key of school inclusion in early childhood education. The inclusive pedagogical practice should be constituted by the junction of the acquired knowledge by the teacher throughout his career and by the availability to seek new ways to do it considering students diversity and their individual characteristics.

Este artigo tem como objetivo desencadear uma reflexão sobre a educação inclusiva na educação infantil, considerando a educação inclusiva como um modelo educacional referendado por políticas públicas, no entanto ainda distante da realidade escolar. A reflexão é no sentido de pensar nas mudanças necessárias desde a educação infantil, por ser esta a primeira etapa da educação básica e período crítico no processo de desenvolvimento e aprendizagem de crianças com deficiência. A construção da escola inclusiva desde a educação infantil implica em pensar em seus espaços, tempos, profissionais, recursos pedagógicos etc., voltados para a possibilidade de acesso, permanência e desenvolvimento pleno também de alunos com deficiências, alunos esses que, em virtude de suas particularidades, apresentam necessidades educacionais que são especiais. O texto aborda, entre outros aspectos, a necessidade de se repensar a prática pedagógica como elemento fundamental de inclusão escolar na educação infantil. A prática pedagógica inclusiva deverá se constituir pela junção do conhecimento adquirido pelo professor ao longo de sua trajetória e da disponibilidade em buscar novas formas de fazer considerando a diversidade dos alunos e as suas características individuais.
Inclusive education in early childhood education
Keywords: Inclusive education; Early childhood education; Pedagogical practice; Educação inclusiva; Educação infantil; Prática pedagógica